Cryptocurrencies and the future of money. Money and trust in Germany - Seiferling, Mike; Ahmed, Thamin; ElBahrawy, Abeer Yehia; Chan, Keith; Padilha, Tales (IE Center for the Governance of Change, 2020)
The euro was established by the provisions of the 1992 Maastricht Treaty, and is now the official currency of 19 of the 28 member states of the European Union, including Germany. It has replaced the previous German currency, Deutsche mark, which ceased to be convertible to euros by 2002. As of today, the euro is the secondlargest reserve currency as well as the second-most traded currency in the world after the US dollar. The euro has even surpassed the US dollar and become the currency with the highest values of banknotes and coins in circulation in the world. As can be seen in Figures 1 and 2 below, the supply of money since 1980 (during both pre and post euro periods) and has a steady increase with stable increase in consumer prices (CPI)
Keywords: Cryptocurrency; Criptomonedas; Policies; Políticas; Perspectives; Perspectivas; Disrupting economy; Economía disruptiva